THE NEED TO ENSURE ECONOMIC SECURITY IN THE HEALTH SECTOR - Mamasolieva Shoxis Abdugapparovna; Karimov Abduxalim Abdurazzaqovich (Web of Journals Publishing, 2024)
This article delves into the critical importance of ensuring economic security in the health sector. By conducting a thorough literature analysis, we explore the various factors influencing economic security in healthcare and propose methods to enhance financial sustainability. The study emphasizes the significance of government investment, robust healthcare policies, and pandemic preparedness to fortify the economic foundations of the health sector. The results and discussions aim to provide insights into creating a resilient healthcare system that can withstand unforeseen challenges while offering suggestions for future improvements.
Keywords: Economic security, health sector, public health, financial sustainability, healthcare infrastructure, pandemic preparedness, government investment, healthcare policy.